Prosthetic Rehabilitation of Cleft Lip Palate with Andrews Bridge Modified as Obturator Prosthesis: Case Report - Murić Almina; Ayvalioglu Demet Cagil; Rohlig Bilge Gokcen (Balkan Stomatological Society, 2020)
Background/Aim: Congenital defects such as cleft palate and lips require a long-lasting and multidisciplinary approach. In cases when surgical and orthodontic treatment is not feasible, prosthodontic management of these patients is advocated. Prosthetic rehabilitation of cleft palate in concerning of achieving aesthetic and function (such as swallowing and speech) outcomes is very demanding.